Effect of age category on the flexibility profile in young taekwondo athletes (Revista de Artes Marciales Asiáticas, 2018)
The main aim of this study was to analyze the effect of the age category on the flexibility profile in young taekwondo athletes, by using angular tests. A total of 17 young taekwondo athletes were recruited, who were classified according to their federative age category. The range of motion of the main movements of the lower extremity was assessed by using the "ROM SPORT" protocol. A descriptive analysis was made of each of the quantitative variables, which included means and standard deviations. A t-test was used to determine the existence of differences between the dominant and non-dominant limbs. In addition, the same statistical test analyzed the interaction between the 11 selected movements and age categories. Finally, the effect size of the results was calculated. The results showed significant differences between cadets and juniors categories in EC (iliopsoas), RIC (external rotators), REC (internal rotators) and total rotation of the hip (sum of RIC and REC). These results are not in tune with other studies that have assessed flexibility in taekwondo. Cadet taekwondo athletes had higher values of flexibility than the junior category in the internal and external rotator muscles and in the psoas-iliac.